Altered Homotopic Connectivity in the Cerebellum Predicts Stereopsis Dysfunction in Patients With Comitant Exotropia - Chen, Fei; Hu, Zhirou; Liu, Hui; Zhen, Fangyuan; Liu, Chenlu; Li, Qiuming (Frontiers in Human Neuroscience, 2022)
Purpose: Comitant exotropia (CE) is common eye disorder characterized by impaired stereoscopic vision and eye deviation. Previous neuroimaging studies demonstrated that CE patients were accompanied by specific functional and structural abnormalities of the brain. However, the effect of impaired stereoscopic vision and eye deviation on interhemispheric homotopic connectivity remains unknown. Methods: A total of thirty-six CE patients (25 males and 11 females) and thirty-six well-matched healthy controls underwent magnetic resonance imaging (fMRI) scanning. The VMHC (voxel-mirrored homotopic connectivity) method was applied to assess the interhemispheric homotopic connectivity changes in CE patients. Furthermore, support vector machine (SVM) method was applied to assess to differentiate patients with CE from HCs with the VMHC maps as a feature. Results: compared with HCs, CE patients showed significantly increased VMHC values in the bilateral cerebelum_ 8 and cerebelum_4_5. Moreover, We found that the VMHC maps showed an accuracy of 81.94%, and area under curve of 0.87 for distinguishing the CE patients from HCs. Conclusion: our study demonstrates that CE patients showed interhemispheric homotopic connectivity changes in the cerebellum, which might be reflect the neurological mechanisms of impaired impaired stereoscopic vision and eye deviation in CE patients.